Understanding the Shift of Educational Paradigms toward Student Centered Learning in Responding to Digital Transformation and Learning Equity Challenges - Pettalongi, Sagaf S.; Chotimah, Yeti; Hidayat, Yasysyar; Dewi, Anggun Tyas Jati (Jurnal Ar Ro'is Mandalika (Armada), 2026)
This study examines the shift towards student-centered learning in response to the challenges of digital transformation and learning equity in education. It aims to explore how this paradigm shift can be effectively implemented across educational institutions, considering the barriers such as digital divides and access to technology. Using a library research methodology, secondary data from relevant literature, policy documents, and previous studies are analyzed to understand the current state of digital integration in education. The findings reveal that while student-centered learning offers significant benefits, its success is limited by unequal access to resources and digital tools, especially in rural and underserved areas. The study concludes that overcoming these barriers requires a coordinated effort from policymakers, educational institutions, and communities to ensure equitable access to technology and professional development for teachers, thus enabling an inclusive educational environment for all students.